2019
DOI: 10.1177/0033294119876076
|View full text |Cite
|
Sign up to set email alerts
|

Work Engagement and Resiliency Impact the Relationship Between Nursing Stress and Burnout

Abstract: Nursing is a stressful occupation, and consequently, nurses are at risk for work-related burnout. This is highly problematic, as numerous negative consequences are associated with burnout. Most notably, burnout may result in nurses leaving the profession, thereby exacerbating the nursing shortage. The purpose of the present study was to advance the understanding of burnout in the nursing profession. Specifically, three types of work engagement (i.e., vigor, dedication, and absorption) and resiliency were hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 52 publications
7
50
1
1
Order By: Relevance
“…This notion is supported by Steinkopf et al [73], who argued that work-related stress and resilience are inversely linked. Further, studies showed that stress among nurses is negatively related to resilience [64]. Therefore, increasing resilience among employees can reduce their job stress due to challenging or threatening conditions, such as the COVID-19 pandemic.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is supported by Steinkopf et al [73], who argued that work-related stress and resilience are inversely linked. Further, studies showed that stress among nurses is negatively related to resilience [64]. Therefore, increasing resilience among employees can reduce their job stress due to challenging or threatening conditions, such as the COVID-19 pandemic.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…When employees do not have family and friends' supports, they may experience work stress. Work stress, which can lead to work disengagement, is said to have a negative significant influence on employee resilience [64]. Research has shown that the buffer for employees to be able to endure chaotic situations is the support from friends and family.…”
Section: Mediating Effects Of Resiliencementioning
confidence: 99%
“…Patients without a risk of delayed discharge underwent DP in a stable condition. This could reduce the burden of nurses doing all of the work at one time on admission, since nursing is a stressful occupation, especially with increasing amounts of overtime [19,20]. It is important to focus on the work environment of nurses to improve their job satisfaction and retention, and thereby decrease healthcare costs by increasing e ciency [21].…”
Section: Discussionmentioning
confidence: 99%
“…Job burnout also has a negative impact on an individual's physical and mental health, and different occupational stress factors may lead to different health problems, and a reduced quality of life [58]. Hetzel et al [59]believed that higher levels of stress are associated with a greater likelihood of negative emotional experience and adverse effects on mental health. Excessive stress levels are likely to lead to job burnout, which thus affects health.…”
Section: Discussionmentioning
confidence: 99%